Les élections présidentielles de 2007 à Timor Leste - Christine Cabasset-Semedo; Frédéric Durand (EchoGéo)
In April-May 2007 presidential elections were held in East-Timor. Since independence (2002), the country crossed several crisis, calling into question the leading role of the Fretilin, the historical party which fought against Indonesia invasion and for independance. The first round of the ballot was tight with three candidates between 19 and 28%. At the end of the second round, opposing Lu-Olo, Fretilin's candidate to José Ramos Horta, former Prime minister, co-Nobel Peace Laureate in 1996, this last has been elected with 69% of the votes. The legislative elections which were held the following month, in June, confirmed the Fretilin weakening and the political rebalancing.